Numerical study on combustion characteristics and heat transfer enhancement of the micro combustor embedded with Y-shaped fin for micro thermo-photovoltaic system. (5th July 2022) - Zhang, Chenghua; Yan, Yunfei; Shen, Kaiming; Gao, Wei; He, Ziqiang; Xue, Zongguo; Li, Jianbo
Highlights: To improve the thermal performance of MTPV, a novel Y-shaped fin is designed and inserted into the micro combustor. Compared with straight fin or without fin, Y-shaped fin brings a better combustion characteristics and heat transfer enhancement. Considering the thermal performance and pressure loss caused by the Y-shaped fin length, 8 mm maintains a better comprehensive performance. Increasing in inlet velocity is conducive to improve the exergy, and 7 m/s can provide an exergy of 19.26 W. Abstract: Aimed at improving the combustion and thermal performance of micro combustor to increase energy output, a Y-shaped fin is designed to enhance the heat transfer. Firstly, the combustion and thermal performance of conventional micro combustor (MC), micro combustor embedded with straight fin (MCESF) and micro combustor embedded with Y-shaped fin (MCEYF) are compared. The results show that the embedding of Y-shaped fin improves the combustion and thermal performance obviously, especially MCEYF has the best comprehensive performance, meanwhile the mean outer wall temperature and the combustion efficiency are up to 1213.3 K and 99.14% at 5 m/s, which are significantly higher than MC and MCESF. Besides, a larger Y-shaped fin length is beneficial to fully enhance the heat transfer, but it directly destroys the temperature uniformity and consumes huge power due to the huge inlet pressure. Although the fin length of 12 mm brings an exergy up to 19.11 W, but the outer wall maximum temperature difference and inlet pressure have reached 181.38 K and 246.38 Pa, and Y-shaped fin with length of 8 mm maintains best comprehensive performance at 5 m/s. In addition, increasing the inlet velocity is conducive to improving the energy conversion, resulting in greater radiation energy and exergy, but it reduces the radiation efficiency and the exergy efficiency, meanwhile bring a huge pressure drop. Exergy increases from 13.68 W to 18.39 W with an inlet velocity from 3 m/s to 8 m/s, but the corresponding exergy efficiency decreases from 50.42% to 25.42%, and the low efficiency causes a large amount of energy to be lost as exhaust gas. Based on the analysis of the combustor material, high thermal conductivity material is beneficial to MTPV system energy conversion, and the combined use of multiple materials is worth considering. This study obtained the combustion and thermal characteristics under the action of Y-shaped fin, providing reference value for the energy conversion improvement of the micro thermo-photovoltaic system.